Effects of managemental system on performance and economy of growing Japanese quails - BURAGOHAIN, R; KALITA, G; SARMA, K; HAZARIKA, P (The Indian Journal of Animal Sciences, 2011)
Growth, carcass characteristics and economics of Japanese quails (Coturnix coturnix japonica) were studied under cage and deep litter system of management using 80 Japanese quail chicks (2-week-old, either sex). They were divided into 2 groups (cage and deep litter) with 2 replicates. Body weight gain (g/week) was higher in female quails irrespective of management system, but cage rearing resulted significantly higher body weight gain in both sexes than DLS. Feed consumption (g/bird/day) was comparable for both the managemental practices. Percentage carcass yields were significantly higher for thigh, back and neck under CSM for both sexes. Significantly higher yields of drumstick and wing in males under cage, and breast and wing in females under DLS was observed. Yield of giblet was proportionately higher in female. Dressing percentage was significantly better for both sexes on cage than the DLS. Significantly lower cost involved in feeding for producing 1 kg live weight gain under cage rearing with better feed conversion ratio (FCR). It may be opined that the best marketing age of the quails for meat purpose is at sixth weeks of age and cage system may be superior to deep litter rearing for optimum growth, carcass yields and economy. Â